Evaluating the Effects of Circuit Training and Motivation on Gender-Specific Waist Reduction in Overweight Populations - Tambunan, Grace Kharisma; Setyawati, Heny; Rahayu, Setya; Priyono, Bambang; Manullang, Jujur Gunawan (Physical Education Theory and Methodology, 2025)
Background. Overweight is a global health problem that is closely associated with an increased risk of cardiovascular and metabolic diseases. Waist circumference, as an indicator of visceral fat, serves as an important parameter for assessing the effectiveness of weight loss interventions. Motivation and exercise type, including circuit training, are believed to play significant roles in the success of weight management programs. Objectives. This study aimed to analyze the influence of motivation, gender, and circuit training methods (isometric and isokinetic) on waist circumference reduction in overweight individuals. Materials and methods. The study employed a 2x2x2 factorial design with a quasi-experimental approach. Forty participants from a fitness center were divided into eight groups based on the combinations of motivation (high and low), gender, and training method (isometric and isokinetic). Waist circumference data were measured before and after the treatment over 16 training sessions, with data analysis performed using three-way ANOVA. Results. Isokinetic training showed higher effectiveness in reducing waist circumference compared to isometric training, with high motivation being a factor that enhanced results. Conversely, gender did not have a substantial effect on waist circumference reduction. Motivation and exercise type had significant main effects (p < 0.001), while a markedinteraction was found between motivation and exercise type (p < 0.01), highlighting the importance of combining these two factors. Conclusions. Motivation and circuit training methods are key factors in the success of waist circumference reduction, with isokinetic training recommended as the primary choice for optimal results. These findings provide practical guidelines for designing more effective and inclusive physical activity-based overweight management programs.